Patella Alta in a Patient with Recurrent Patellar Dislocation - Alessandro Schneebeli; Marco Barbero (Archives of Sports Medicine and Physiotherapy - Peertechz Publications, 2016)
The patient was a 26-year-old man who was referred to a physical therapist by an orthopedic surgeon for the management of recurrent bilateral patellar dislocations. The patient reported a high rate of dislocation events in the right knee and the last episode, one month before, involved both the patellas.The patient was a mechanic and the high activity level at the work place involved especially kneel positions.At the initial evaluation, the patient complained about moderate pain on the anterior surface of the right knee and fear of new events of dislocation.Visual inspection revealed a bilateral valgus knee (Figure1) and, during walking, an inability to bear weight on the right leg. Assessment of the ankle region reveal a pronated position of both ankles. No other restriction or limitation were noted.